Computational study of copper–gallium disulphide‐based solar cell devices by using CdS and ZnSe buffer layers. Issue 5 (1st September 2014) - Singh, Pravesh; Gautam, Ruchita; Sharma, Sheetal; Kumari, Sarita; Verma, Ajay Singh
Abstract : The authors have performed ab‐initio calculations for the structural, electronic, optical, elastic and thermal properties of the copper–gallium disulphide (CuGaS2 ). The accurate full potential linearised augmented plane wave method was used to find the equilibrium structural parameters and to compute the full elastic tensors. They have reported electronic and optical properties with the recently developed density functional theory of Tran and Blaha. Furthermore, optical features such as dielectric functions, refractive indices, extinction coefficient, optical reflectivity, absorption coefficients and optical conductivities were calculated for photon energies up to 30 eV. The thermodynamical properties such as thermal expansion, heat capacity, Debye temperature, entropy and Grüneisen parameter, bulk modulus and hardness were calculated employing the quasi‐harmonic Debye model at different temperatures (0–1200 K) and pressures (0–8 GPa) and the results are interpreted. Further, CuGaS2 solar cell devices have been modelled; device physics and performance parameters were analysed for CdS and ZnSe buffer layers. Simulation results for CuGaS2 thin layer solar cell show the maximum efficiency (20.5%) with ZnSe as the buffer layer. Most of the investigated parameters are reported for the first time.